Rethinking faith : a constructive practical theology - Poling, James N. (James Newton), 1942- (Minneapolis : Fortress Press, 2011)
What can practical theology contribute to other theological disciplines and the church about the nature of God and the church's witness to Jesus Christ in the world? What can we learn about the love and power of God in Jesus Christ from the community of survivors of violence? Rethinking Faith urges all Christians to consider themselves practical theologians by drawing on their own experiences in making theological assertions. Poling couples his understanding of the tradition with his work with survivors of violence to demonstrate the resilience of Christianity.
The forming God -- The reality of evil and sin -- Christology and the question of salvation -- Constructing a process Christology -- Faithful churches empowered by the Holy Spirit -- Eschatology : theologies of hope -- Congregational practices of hope -- Conclusion : The beauty of God -- Appendix 1 : Methods of practical theology for congregations and church leaders -- Appendix 2 : Methods of practical theology for teachers and scholars
Includes bibliographical references and indexes.
Keywords: Theology, Doctrinal; Practical theology